ANALYSIS OF CHANGES IN THE GENERAL BLOOD COUNT IN CHILDREN UNDER SIX YEARS OF AGE - Berdiyarova Shokhida Shukurullayevna; Diamatova Dinora Norqobil qizi; Niyatqulov Diyorbek G`ayratovich (TADQIQOTLAR.UZ, 2024)
Annotation. Blood tests are probably the most frequently asked tests. This is an integral element of any examination, both at the stage of diagnosis and during treatment. All the links in this system are interconnected and interdependent. Blood consists of a liquid part – plasma and shaped elements – blood cells. Blood washes all cells and tissues of the body, participates in the transport of food and oxygen, the removal of end products of metabolism, etc. Plasma contains proteins, enzymes, hormones, minerals and others. Blood cells have unique characteristics and a certain life span.